Mediating role of career commitment in the relationship of promotional opportunities, rewards and career success - Pasha, Ahmad Tisman; Hamid, Kamal; Shahzad, Arfan (PJSOR, 2017)
The objective of the study is to investigate the mediating role of career commitment between career development practices and career success of employee in insurance sector of Pakistan. Survey method was adopted to collect the data form 374 employees working in insurance sector systematic sampling.PLS-SEM technique was used using Smart PLS 2.0 to analyze the data. Findings of the study suggests that employees’ career development practices have positive relationship with career commitment and career success. Career commitment also have a positive relation with career success. Finally, career commitment mediates the positive role between career development practices and career of insurance sector employees. The effect of career development practices on career commitment and effect of career development practices on career success has been checked in past studies but the mediating role of career commitment particularly for the employees of insurance sector has not been checked before